The impact of disruptive innovation on creative workers: the case of photographers. Issue 2 (4th August 2021) - Williams, Penny; McDonald, Paula; Mayes, Robyn
Abstract: The actual and potential impacts of technological disruption on established organisations and industries have received considerable attention. Yet, impacts on individual workers and professional groups, including in the creative sector that is at the forefront of disruption, remain under-examined. This study draws on in-depth interviews with professional photographers to explore how the convergence of technological innovations, digital media and crowdsourcing platform businesses have changed the nature of photographic work and employment in the industry, and how photographers have responded. The findings reveal that disruptive innovations have profoundly altered labour market dynamics, the value ascribed to photography services and the professional identity of photographers themselves. The implications for workers, including self-employed freelancers, are significant, especially in terms of social and economic opportunities and rights and protections. More broadly, the study contributes to the emerging literature on technology, disruption and the future of work.